GERAKAN MAHASISWA UNTUK PENCEGAHAN PENYEBARAN COVID-19 DI KOTA PADANG - Abdul Hakam; Aisya Wahyuni; Putri Dwiza Arinda; Rahmi Syafira Lista; Fajri Oktaviana Lestari; Helfial Arrizky; Fathinatul Atika; Ajeng Sekar Dewana; Afifah Khairani Arsal; Aldira Putri Azurra; Ayu Hidayati Putri; Naufal Farhah; Salma Wahid Zaidir; Iqbal Zakhaira; Raynaldi Raynaldi; Muhammad Thariqjabbar Hape; Sonya La Vidaloka; Redho Alfaro Zamel; Atiqah Putri Riyan; Dwike Adillah; Rayhan Maghensky (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The outbreak of the Covid-19 pandemic to Indonesia, including the city of Padang, resulted in educational activities at Andalas University having to follow general conditions. The lecture continues even though it is conducted in cyberspace. Higher education activities at Andalas University must continue even though they exist in the real and virtual world but in essence, still produce real products, namely humans who believe and fear God Almighty and have noble, healthy, knowledgeable, capable, creative, independent, skilled, competent and cultured for the benefit of the nation. In addition, higher education activities must also realize the application of science to a society based on reasoning and research work that is useful in advancing the nation's general welfare and intellectual life. By adhering to the mandate of higher education to achieve these educational goals, engineering applications have been made to the public to reduce the impact due to the handling of Covid-19 in Padang City. This activity is participating in distributing foodstuffs to people who are severely affected by the Covid-19 pandemic and helping to reduce the spread by providing hand sanitizer in places where people can potentially gather. This contribution also helps educate the public to reduce the risk of the impact of Covid-19 by designing, creating, and distributing healthy educational materials in cyberspace. This activity has been successfully carried out to participate in dealing with the problem of the Covid-19 pandemic and is still ongoing with the spirit of learning and working from home; maintaining distance is the best way to break the chain of spreading this virus by working well together between the academic community of Andalas University with the Government and Society.